Cognitive Reserve and Anxiety Interactions Play a Fundamental Role in the Response to the Stress - García-Moreno, Jose A.; Cañadas-Pérez, Fernando; García-García, Juan; Roldan-Tapia, María D. (Frontiers in Psychology, 2021)
The aims of the present study were to assess the possible interaction between Cognitive Reserve (CR) and State Anxiety (SA) on adrenocortical and physiological responses in coping situations. Forty healthy, middle-aged men completed the Cognitive Reserve Scale and the State-Trait Anxiety Inventory. We used an Observational Fear Conditioning (OFC) paradigm in order to assess emotional learning and to induce stress. Electrodermal activity (EDA) and salivary cortisol concentrations were measured throughout the conditions. Our results indicate that those who indicated having higher state anxiety showed a lower capacity for learning the contingency, along with presenting higher salivary cortisol peak response following the observational fear-conditioning paradigm. The most prominent finding was the interaction between cognitive reserve and state anxiety on cortisol response to the post observational fear-conditioning paradigm. Given these results, we postulate that the state anxiety reported by participants, reflects emotional activation that hinders the attention needed to process and associate emotional stimuli. However, cognitive reserve has an indirect relation with conditioning, enabling better emotional learning. In this context, cognitive reserve demonstrated a protective effect on hormonal response in coping situations, when reported anxiety or emotional activation were high. These findings suggest that cognitive reserve could be used as a tool to deal with the effects of stressors in life situations, limiting development of the allostatic load.